Implementation of Financial Management in Garlic Farming: Case Study of Garlic Farmers in Cipendawa Village, Pacet, Cianjur, West Java - Waluyo, Tri (Budapest International Research and Critics University, 2022)
Efficient farming is farming with high productivity. This can be achieved if the management of the farm is managed properly. Thus, it is hoped that the results of farming will increase significantly. This research aims to analyze the implementation of financial management in garlic farming. The research was conducted in Cipendawa Village, Pacet, Cianjur, West Java from March to May 2021. The respondents interviewed were 13 garlic farmers. The data then were analyzed by income analysis and calculation of the R/C ratio. The results showed that the largest average income was the garlic farming business with an intercropping pattern of Rp. 33,903,475. Meanwhile, R/C ratio in garlic farming with an intercropping pattern (2.17) is larger than that in cropping pattern monoculture (1.71). It indicated that garlic farming using an intercropping pattern was more profitable than a monoculture cropping pattern.